2001
DOI: 10.1007/s00276-001-0045-7
|View full text |Cite
|
Sign up to set email alerts
|

Papillary muscles and tendinous cords of the right ventricle of the human heart morphological characteristics

Abstract: A series of 79 normal human hearts was studied focusing on the morphological characteristics of the papillary muscles of the right ventricle and their tendinous cords (chordae tendineae). The number, incidence, length and shape of the anterior, septal and posterior papillary muscles were observed. The tendinous cords attached to each papillary muscle were counted at their origin. The papillary muscles and the tendinous cords were measured in situ and after the removal of the right atrioventricular valve (tricu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
34
3
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 9 publications
16
34
3
1
Order By: Relevance
“…These values are almost similar to those found by Nigri et al 8 . However, these authors 8 also found arched and wavy type of APM in 4.3% and 1% of cases respectively.…”
Section: Anterior Papillary Muscle (Apm)supporting
confidence: 92%
See 3 more Smart Citations
“…These values are almost similar to those found by Nigri et al 8 . However, these authors 8 also found arched and wavy type of APM in 4.3% and 1% of cases respectively.…”
Section: Anterior Papillary Muscle (Apm)supporting
confidence: 92%
“…2,8,9,10 Number of heads ranged from 1 to 3 in the present study which is in conformation with the standard text books of anatomy. 2,9,10 Four heads of Ppm were seen only in the study by Nigri et al 8 The incidence of two heads of Ppm is the most common arrangement found in the present study as well as others. 8 The incidence of 3 heads was 33% in the present study, which is higher as compared to the Caucasian study 8 (20%).…”
Section: Posterior Papillary Muscle (Ppm)supporting
confidence: 69%
See 2 more Smart Citations
“…It was single headed in 16 cases, double headed in 26 Cases. Nigri GR et al in 2001 [15] studied the morphological characteristics of the papillary muscles and tendinous cords of the right ventricle in 79 normal human hearts. They observed the number, incidence, length and shape of the anterior, septal, and posterior papillary muscles and they counted the tendinous cords attached to each papillary muscle at their origin.…”
Section: Discussionmentioning
confidence: 99%